The half-stitched Amish quilting club (Half-stitched Amish quilting club, 1,, 2013)
Stitch by stitch, six unlikely lives are transformed with a little help from an Amish widow's quilting classes. . .and the healing hand of God. Annotation: Stitch by stitch, six unlikely lives are transformed with a little help from an Amish widow's quilting classes. . .and the healing hand of God.

The tattered quilt (Half-stitched Amish quilting club, 2,, 2013)
Join Emma Yoder Miller, the Amish widow-turned-newlywed, as she leads another quilting class with a new group of unlikely students, all with tattered pieces of their lives that need mending. Members of the patchwork group find friendship, faith, healing, and restoration while gathered around their quilts, under the Father's guiding hands - for only He can take what's ragged and shabby from the lives of His children and turn it into beauty for His glory.

The healing quilt (Half-stitched Amish quilting club, 3,, 2019)
Retired Amish newlyweds Emma and Lamar Miller start a new quilting class, in which they work with an unlikely group of students to achieve emotional healing and create beautiful traditional quilts.